2014
DOI: 10.1093/abbs/gmt124
|View full text |Cite
|
Sign up to set email alerts
|

MiR-181c modulates the proliferation, migration, and invasion of neuroblastoma cells by targeting Smad7

Abstract: MicroRNAs (miRNAs) function as key regulators of gene expression in various cancers. In this study, the aim is to explore the roles and regulation mechanism of miR-181c in neuroblastoma (NB) cells. We found that miR-181c was downregulated in metastatic NB tissues, compared with primary NB tissues. Then functional studies indicated that miR-181c overexpression inhibited NB cell proliferation, migration, and invasion, while miR-181c inhibition increased cell proliferation, migration, and invasion. EGFP reporter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 29 publications
5
27
0
Order By: Relevance
“…In addition, miR‐181c also apparently alleviated CsA‐caused renal damage and fibrosis in vivo , strongly suggesting that miR‐181c may play critical roles in EMT‐associated biological processes. Our speculation was supported by increased evidences showing that miR‐181c inhibited morphology‐related traits in several tumor models such as gastric cancer and neuroblastoma through affecting the EMT process . For example, miR‐181c inhibited glioblastoma cell invasion, migration, and mesenchymal transition by targeting the TGF‐β pathway and miR‐181c inhibited the migration and invasion of neuroblastoma cells by targeting Smad7 .…”
Section: Discussionsupporting
confidence: 55%
“…In addition, miR‐181c also apparently alleviated CsA‐caused renal damage and fibrosis in vivo , strongly suggesting that miR‐181c may play critical roles in EMT‐associated biological processes. Our speculation was supported by increased evidences showing that miR‐181c inhibited morphology‐related traits in several tumor models such as gastric cancer and neuroblastoma through affecting the EMT process . For example, miR‐181c inhibited glioblastoma cell invasion, migration, and mesenchymal transition by targeting the TGF‐β pathway and miR‐181c inhibited the migration and invasion of neuroblastoma cells by targeting Smad7 .…”
Section: Discussionsupporting
confidence: 55%
“…It is required to breakdown ECM for cell migration and cancer metastasis [35]. On the other hand, the inhibition of miR-181c expression could increase cell migration, and invasion in neuroblastoma cells [36], whereas overexpression of miR-10a enhanced the metastatic potential of many cancer cells [37,38]. These results support our findings that miR-181c inhibition and miR-10a overexpression may downregulate Col1 production.…”
Section: Discussionsupporting
confidence: 85%
“…Through imperfect sequence-specific binding to the 3′-UTR of target mRNAs, miRNAs down-regulate gene expression by degrading target mRNAs [26], [27] and/or inhibiting translation [28]. The present study demonstrated that inhibition of miR-92a significantly increased protein levels of SMAD7, but did not affect Smad7 mRNA levels, indicating that miR-92a inhibits the protein translation at the post-transcriptional level, but does not promote Smad7 mRNA degradation.…”
Section: Discussionmentioning
confidence: 47%